1998
DOI: 10.1111/j.1749-6632.1998.tb09605.x
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic, Neuroendocrine, and Immune Responses to Psychological Stress: The Reactivity Hypothesisa

Abstract: We examined the effects of brief psychological stressors on cardiovascular, neuroendocrine, and cellular immune response in 22 older women to investigate the common effects of stress across systems. Results revealed that psychological stressors heightened cardiac sympathetic activation, elevated plasma catecholamine concentrations, and affected the cellular immune response (ps < 0.05). In a replication and extension, 27 women caring for a spouse with a progressive dementia (high chronic stress) and 37 controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
155
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(163 citation statements)
references
References 35 publications
5
155
0
3
Order By: Relevance
“…It has been reported that individuals with lower T-cell responses, measured by the influenza-virus-specific IL-2 production in vitro three months following influenza vaccination, exhibited larger pre-ejection period reactions to mental arithmetic and speech tasks (11,12). However, the analysis was based on eight female participants with a mean age of 67 years, clearly a very different sample in terms of size and characteristics to the present one.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…It has been reported that individuals with lower T-cell responses, measured by the influenza-virus-specific IL-2 production in vitro three months following influenza vaccination, exhibited larger pre-ejection period reactions to mental arithmetic and speech tasks (11,12). However, the analysis was based on eight female participants with a mean age of 67 years, clearly a very different sample in terms of size and characteristics to the present one.…”
Section: Discussionmentioning
confidence: 63%
“…In the first, elderly women with lower T-cell responses three months following influenza vaccination were reported to exhibit relatively large cardiac reactions to standard laboratory stress tasks (11,12). In the second, a study of hepatitis B vaccination, participants with lower antibody titres following vaccination showed larger cardiac output and contractility reactions, but smaller increases in total peripheral resistance to mental arithmetic stress (13).…”
mentioning
confidence: 99%
“…Previous studies have shown that religion-mediated social support is linked to lower morbidity but not specifically to cardiovascular inflammation in people with diabetes (28,29). Another explanation that may explain the study results is that religious attendance is associated with lower rates of anxiety and stress and may reduce CRP levels through neurohormonal mechanisms (6,8,30). Elevated CRP levels are associated with blunted endothelial vasoreactivity and impaired vascular relaxation, an effect that has been linked to insulin resistance (13).…”
Section: Analysis Planmentioning
confidence: 72%
“…Perhaps elevated TNF-α levels in low-locomotion, lowglucocorticoid individuals may serve as a protective advantage for certain disease processes like parasite infections (Derouich-Guergour et al, 2001), and/or a risk factor for others diseases, like rheumatoid arthritis, multiple sclerosis, and irritable bowel disease (Inglis et al, 2005;Issekutz et al, 1994;. A stronger immune challenge with longer monitoring of pro-inflammatory cytokines would provide more clear results, and immune measures later in the life span after repeated elevated glucocorticoid exposure may provide the most accurate picture of potential immune function alteration in females with different behavioral temperaments (Cacioppo et al, 1998). The suggestion that thymus size and plasma TNF-α levels may differ among young females of different behavioral tendencies provides support for further work in this area.…”
Section: Discussionmentioning
confidence: 99%